Algoritma Penyelesaian Sistem Persamaan Linear Fuzzy Dan Implementasinya Pada Bahasa C++ - Syahnur, Muslim; Ahmad, Defri (Journal of Mathematics UNP, 2024)
A system of fuzzy linear equations is a linear equation with more than one number that is related to one another where the constants and variables are in the form of fuzzy numbers. To solve it, the system of fuzzy linear equations is changed to a system of non-fuzzy linear equations and the solution uses codeblock program software to get fast and accurate results. In solving the system of fuzzy linear equations in this study, the Crout decomposition method was applied and developed an algorithm to be applied to the C++ language. Crout's decomposition method is to decompose a matrix into a multiplication matrix ???????? where the matrix ???? (Lower) is the lower triangular matrix and the matrix ???? (Upper) is the upper triangular matrix whose main diagonal has a value of one. The results of the research are in the form of programs that can find solutions to systems of fuzzy linear equations that have fulfilled the complexity of the function.